UVIT observations of UV-Bright stars in four Galactic Globular Clusters. Issue Volume 14:Issue S351(2019) (May 2019) - Kumar, Ranjan; Pradhan, Ananta C.; Parthasarathy, M.; Ojha, Devendra K.; Mohapatra, Abhisek; Murthy, Jayant
Abstract: We have performed photometric analysis of four Galactic globular clusters (GGCs): NGC 4147, NGC 4590, NGC 5053 and NGC 7492 using far-UV and near-UV filters of the Ultraviolet Imaging Telescope (UVIT) on-board AstroSat. With the help of color-magnitude diagrams (CMDs), we have identified 150 blue horizontal branch stars (BHBs), and 40 blue straggler stars (BSS) in the four GGCs. We study the temperature and radial distribution of BHBs and BSS for the four GGCs.